1977
DOI: 10.1073/pnas.74.9.3988
|View full text |Cite
|
Sign up to set email alerts
|

A postsynthetic modification of human α-fetoprotein controls its immunosuppressive potency

Abstract: In MATERIALS AND METHODSSerum (500 cm3) was obtained by plasmapheresis from patient Od, who had advanced hepatoma, 2 weeks prior to death. Ascitic fluid (2000 cm3) and tumor tissue (300 g) were obtained at autopsy. The tumor tissue was homogenized in 5 volumes of 10 mM phosphate-buffered 0.15 M NaCl (pH 7.4) and cleared of particulate matter by ultracentrifugation at 120,000 X g for 2 hr. Concentrations of a-fetoprotein in the serum, ascitic fluid, and tumor homogenate were 200, 150, and 50,gg/ml, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1979
1979
1997
1997

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Although a physiological function of AFP is still uncertain, studies from the laboratory of Yachnin et al (Lester et al, , 1977(Lester et al, , 1978bYachnin and Lester, 1976) have demonstrated potent immunosuppressive effects of human AFP in fetal serum, fetal tissue extracts and ascitic fluid of hepatoma patients. The immunosuppressive activity was found to be several orders of magnitude higher in the fetus, with the most potent preparations isolated from fetuses at 10-20 weeks of gestation (a period of fetal development characterized by a preponderance of isoform 11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a physiological function of AFP is still uncertain, studies from the laboratory of Yachnin et al (Lester et al, , 1977(Lester et al, , 1978bYachnin and Lester, 1976) have demonstrated potent immunosuppressive effects of human AFP in fetal serum, fetal tissue extracts and ascitic fluid of hepatoma patients. The immunosuppressive activity was found to be several orders of magnitude higher in the fetus, with the most potent preparations isolated from fetuses at 10-20 weeks of gestation (a period of fetal development characterized by a preponderance of isoform 11).…”
Section: Discussionmentioning
confidence: 99%
“…The immunosuppressive activity was found to be several orders of magnitude higher in the fetus, with the most potent preparations isolated from fetuses at 10-20 weeks of gestation (a period of fetal development characterized by a preponderance of isoform 11). Furthermore, the most electronegative isoform of AFP identified by these investigators proved to be the most potent immunosuppresant (Lester et al, , 1977(Lester et al, , 1978b. No correlation was found between the carbohydrate content and the immunosuppupresant potency of the AFP isoform preparations, suggesting that some other charged moiety (fatty acids?)…”
Section: Discussionmentioning
confidence: 99%
“…In our case, the source of AFP may change the proportions of variants. According to Lester et al [24], HAFP isolated from the serum and ascitic fluid of hepatoma-bearing patients and from fetal liver varied in biological potency by over three orders of magnitude. Furthermore, they demonstrated the existence of three molecular species of HAFP, and the quantitation of these three species revealed a correlation between the relative amount of the most electronegative species and immunosuppressive activity.…”
Section: Discussionmentioning
confidence: 99%
“…Yachnin [8] found that the fetalderived human protein strongly inhibited the phytohemagglutinin-stimulated response of peripheral lymphocytes but AFP from the serum and ascites fluid of a hepatoma pa tient was less active. In other studies Lester et al [9] showed that AFP from fetal liver and from a hepatoma extract had over 100 times the activity of the protein isolated from the serum of the patient and approxi mately 500 times that isolated from the as cites fluid. Human AFP has been reported to suppress la-associated T cell proliferation in vitro [10].…”
mentioning
confidence: 99%